2013
DOI: 10.1007/s10103-013-1288-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of optical spectroscopy for in vivo detection of cervical pre-cancer

Abstract: In order to investigate the effectiveness of optical spectroscopy for in vivo diagnosis of cervical pre-cancerous conditions, a series of published studies are surveyed. The six optical technologies investigated include fluorescence spectroscopy, reflectance spectroscopy, and their combination using point probe or multispectral imaging approaches. Searching in the well-known databases, the most recent published works were sought out. Various aspects of the studies were evaluated including the details of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…29 However, fewer studies have been conducted to evaluate the CIN detection capability by reflectance spectroscopy alone using a white light source. 6 The present study showed good potential of reflectance spectroscopy using a very simple system incorporating only a white light source, a spectrophotometer and a single optical fiber in cervical tissue diagnosis. Also, very quick measurement of less than one second makes it a real-time tool as an adjunct to colposcopy routine in clinics.…”
Section: System Simplicitymentioning
confidence: 66%
See 2 more Smart Citations
“…29 However, fewer studies have been conducted to evaluate the CIN detection capability by reflectance spectroscopy alone using a white light source. 6 The present study showed good potential of reflectance spectroscopy using a very simple system incorporating only a white light source, a spectrophotometer and a single optical fiber in cervical tissue diagnosis. Also, very quick measurement of less than one second makes it a real-time tool as an adjunct to colposcopy routine in clinics.…”
Section: System Simplicitymentioning
confidence: 66%
“…Unlike other researches in which at least five optical fibers 6 were gathered in a probe to illuminate the tissue and collect the reflected light or the fluorescence spectra from it, the method introduced in this paper utilized only a single fiber. The small probe dimension and use of one optical fiber have the advantages of low cost, system simplicity and easier service and maintenance procedures.…”
Section: System Simplicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Optical spectroscopy has been thoroughly studied over the past years to characterize its diagnostic accuracy in diagnosing microcirculation disorders [19] or cancer on a wide variety of organs such as liver [20,21], breast [13], colon [9,22], skin [3,23,24], cervix [25,26], esophagus [27] or bronchi [28]. Those research teams decided either to use off-the shelf devices, or to develop their own devices.…”
Section: Introductionmentioning
confidence: 99%